Central nervous system tumours among adolescents and young adults (15–39 years) in Southern and Eastern Europe: Registration improvements reveal higher incidence rates compared to the US. (November 2017) - Georgakis, Marios K.; Panagopoulou, Paraskevi; Papathoma, Paraskevi; Tragiannidis, Athanasios; Ryzhov, Anton; Zivkovic-Perisic, Snezana; Eser, Sultan; Taraszkiewicz, Łukasz; Sekerija, Mario; Žagar, Tina; Antunes, Luis; Zborovskaya, Anna; et al.
Abstract: Aim: To present incidence of central nervous system (CNS) tumours among adolescents and young adults (AYAs; 15–39 years) derived from registries of Southern and Eastern Europe (SEE) in comparison to the Surveillance, Epidemiology and End Results (SEER), US and explore changes due to etiological parameters or registration improvement via evaluating time trends. Methods: Diagnoses of 11, 438 incident malignant CNS tumours in AYAs (1990–2014) were retrieved from 14 collaborating SEE cancer registries and 13, 573 from the publicly available SEER database (1990–2012). Age-adjusted incidence rates (AIRs) were calculated; Poisson and joinpoint regression analyses were performed for temporal trends. Results: The overall AIR of malignant CNS tumours among AYAs was higher in SEE (28.1/million) compared to SEER (24.7/million). Astrocytomas comprised almost half of the cases in both regions, albeit the higher proportion of unspecified cases in SEE registries (30% versus 2.5% in SEER). Similar were the age and gender distributions across SEE and SEER with a male-to-female ratio of 1.3 and an overall increase of incidence by age. Increasing temporal trends in incidence were documented in four SEE registries (Greater Poland, Portugal North, Turkey-Izmir and Ukraine) versus an annual decrease in Croatia (−2.5%) and a rather stable rate in SEER (−0.3%). Conclusion: This first report on descriptive epidemiology of AYAs malignant CNS tumours in the SEE area shows higher incidence rates as compared to the United States of America and variable temporal trends that may be linked to registration improvements. Hence, it emphasises the need for optimisation of cancer registration processes, as to enable the in-depth evaluation of the observed patterns by disease subtype. Highlights: Malignant central nervous system tumours incidence in adolescents and young adults in Southern and Eastern Europe was higher compared to the US. Variable temporal trends were recorded mainly attributed to the improvement of cancer registration. Astrocytomas comprised half of malignant central nervous system tumours in both regions. A male preponderance and an increasing incidence with age were similarly recorded in both regions. The high proportion of unspecified cases necessitates the optimisation of cancer registration in Southern and Eastern Europe.